2018
DOI: 10.1155/2018/4240178
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management Training (SMT) Improves Coping of Tremor-Boosting Psychosocial Stressors and Depression in Patients with Parkinson’s Disease: A Controlled Prospective Study

Abstract: Background Stress reduction and relaxation exercises are therapeutically suggested to patients with Parkinson's disease (PD) and tremor, but data regarding efficacy or preferential methods are missing. Objective To investigate the effect of a standardized stress management training (SMT) according to Kaluza on coping with tremor-boosting psychosocial stress factors. Methods 8-week SMT was applied to 82 PD patients with tremor and 30 controls. Changes in stress-associated factors were measured applying four sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(59 reference statements)
0
2
0
1
Order By: Relevance
“…Detecting these specific anomalies can help with PD diagnosis. It have been reported that mindfulness-based intervention ( 81 , 82 ), stress management training ( 83 ) and Mind-Body technique (relaxation guided imagery) ( 84 , 85 ) may help in the alleviation of both motor and non-motor symptoms as well as the slowing of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting these specific anomalies can help with PD diagnosis. It have been reported that mindfulness-based intervention ( 81 , 82 ), stress management training ( 83 ) and Mind-Body technique (relaxation guided imagery) ( 84 , 85 ) may help in the alleviation of both motor and non-motor symptoms as well as the slowing of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Tremors in individuals with PD are exacerbated when they are mentally and emotionally stressed (Schlesinger et al, 2009 ; Buhmann et al, 2018 ), and conversely reduced during mental relaxation; disappearing in sleep (Poliaková and Králová, 2015 ). The key to curtailing tremors may be to provide patients with a relaxed state of mind (Punkanen and Ala-Ruona, 2012 ).…”
Section: The Relaxation Hypothesismentioning
confidence: 99%
“…Darüber hinaus werden in der PTK Einführungskurse in Techniken zur Stressbewältigung angeboten, z. B. nach Kaluza, Autogenes Training, Yoga, Tai Chi sowie LSVT ® BIG oder Musiktherapie, die nachweislich die motorischen und nichtmotorischen Funktionen verbessern [13][14][15][16]. Ziel ist es, Patienten zu motivieren, ausgewählte Verfahren im Alltag regelmäßig therapeutisch zu nutzen.…”
Section: Vor-/ Nachteile Des Ptk-konzepts Gegenüber Ambulanten Behandunclassified